1993
DOI: 10.1524/stuf.1993.46.14.3
|View full text |Cite
|
Sign up to set email alerts
|

Language universale and linguistic typology: data-bases and explanations

Abstract: ZusammenfassungDer Aufsatz bespricht zwei wichtige Aspekte der Sprachtypologie und Universalienforschung: die Datenbasis für typologische Untersuchungen und das Problem der Erklärung sprachlicher Universalien. Was die Datenbasis betrifft, wird die Wichtigkeit "unabhängiger Fälle" unterstrichen, eine Forderung, die der Gebrauch von Stichproben mit genetischem Gleichgewicht nur teilweise erfüllt. Besonders wichtige Möglichkeiten für unabhängige Fälle liegen in Kreolsprachen und Gebärdensprachen, sowie in der Var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
191
0
36

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(229 citation statements)
references
References 1 publication
2
191
0
36
Order By: Relevance
“…The key insight is that this new causal link can be interpreted either as initial in the overall causal structure -deriving a causative reading -or intermediary -deriving an instrumental reading. The idea that causatives introduce a new initial causal event is the standard analysis, and the idea that instruments are intermediary causees has been claimed in several previous works (Talmy 1976, Comrie 1989, Croft 1991, Ichihashi-Nakayama 1996, Goldberg 2002, Peterson 2007, Koenig et al 2008. For example, Van Valin & Wilkins (1996) argue that agent, force (cause), and instrument all derive from a broader effector role and differ only in both properties of the NP and their position in the causal sequence described by the verb.…”
Section: Theoretical Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…The key insight is that this new causal link can be interpreted either as initial in the overall causal structure -deriving a causative reading -or intermediary -deriving an instrumental reading. The idea that causatives introduce a new initial causal event is the standard analysis, and the idea that instruments are intermediary causees has been claimed in several previous works (Talmy 1976, Comrie 1989, Croft 1991, Ichihashi-Nakayama 1996, Goldberg 2002, Peterson 2007, Koenig et al 2008. For example, Van Valin & Wilkins (1996) argue that agent, force (cause), and instrument all derive from a broader effector role and differ only in both properties of the NP and their position in the causal sequence described by the verb.…”
Section: Theoretical Preliminariesmentioning
confidence: 99%
“…In many languages, the demoted causee in causative constructions is marked with some kind of distinct oblique morphology (Comrie 1989). With -ish, however, there is no such marking on the demoted causee.…”
mentioning
confidence: 99%
“…We found that the assignment primarily follows a simple (semantic) principle which is based on the control asymmetry between referents of noun phrases: one can rank each argument of a verb by the greater or lesser degree of control that its referent exerts, or intends to exert, over the referents of the other argument(s). Strength of control is a continuum (Comrie, 1981; but also see note 18), depends on the semantics of the verb and is reflected in its case role properties (or theta-features). 17 Strength 15 The three subpatterns of PH1 only differ by the number of NP-arguments: they can easily be collapsed into NP 1 -V-(NP 2 -(NP 2 ) ).…”
Section: Utterance Organizationmentioning
confidence: 99%
“…These two factors must be carefully kept apart, although in practice they often go hand in hand. The topicfocus-structure reflects the fact that a part of the utterance defines a set of alternatives to be decided (the 'topic') and then selects one 18 This argument is certainly in a semantic relation to the verb -it has a 'case role' or 'thetarole' -and can be 'in control" in the sense that Comrie (1981) uses this term, but (i) there is no control asymmetry, and (ii) the semantic relation remains constant whether the argument is preverbal or postverbal (pattern PH1: 'Charlie arrive' or pattern PH3: 'arrive Charlie'). of those which is claimed to hold (the 'focus').…”
Section: Sem2 Controller Of Source State Outweighs Controller Of Targmentioning
confidence: 99%
“…Another issue relating to the present thesis is linguistic typology and universals (Greenberg 1963;Comrie 1989). Clyne (1991: 157) argues for "the theoretical gains that could be derived from studying languages of different typologies all in contact with the same language (English)" (e.g., Clyne 1967; Pauwels 1991 [Dutch in Australia); Bettoni 1981 [Italian in Australia]; Tamisl988, 1990Tamisl988, , 1991 Haugen 1956; Scotton and Okeju 1973 [Ateso in Africa]).…”
Section: Points To Notementioning
confidence: 99%